Specific Protein Targeting during Cell Differentiation: Polarized Localization of Fus1p during Mating Depends on Chs5p in Saccharomyces cerevisiae - Santos, Beatriz (American Society for Microbiology, 2003)
In budding yeast, chs5 mutants are defective in chitin synthesis and cell fusion during mating. Chs5p is a late-Golgi protein required for the polarized transport of the chitin synthase Chs3p to the membrane. Here we show that Chs5p is also essential for the polarized targeting of Fus1p, but not of other cell fusion proteins, to the membrane during mating.